ETHNOOCEANOGRAPHY DAN TITIK TEMU ASPEK SYARâ€™I DALAM PENENTUAN AWAL BULAN RAMADHAN DAN SYAWAL OLEH JOGURU KESULTANAN TIDORE - Salnuddin, Salnuddin; Nurjaya, I Wayan; Jaya, Indra; Natih, Nyoman M.N (Al-Ahkam, 2017)
Ethnooceanography and the intersection of shar'i aspects to determination of the early of Ramadan and Shawwal by Joguru Sultanate of Tidore. The determination of the early of the new month of Ramadan and Shawwal was very important for Muslims because it is related to the time of worship. Judge syara 'The Sultanate of Tidore (Joguru) has long applied the method of determining the early month of Hijri (Ramadan and Shawwal) through tidal movement observed on "akebai" included in ethooceanography and called Joguru Method (MJ). Hilal that has never been seen in Tidore and its surrounding areas in the long-term cycle of moon (34 years) caused its early moon to be inapplicable due to non-fulfillment of the requirement of hisab (hadith). MJ makes observation (rukyat) change of tidal movement on "akebai" is "ijtihÄd". The appropriateness of the scientific aspects of ethnoocaenography and the intersection of the shar'i aspects make it a comparative method of determining the beginning of the new month of Hijri in astronomy (hilÄl). Required the expansion of the meaning of the â€œhilÄlâ€ as an indicator of the beginning of the month of the Hijri calendar.[]Ethnooceanography dan titik temu aspek Syarâ€™i dalam penentuan awal bulan Ramadhan dan Syawal oleh Joguru Kesultanan Tidore. Penentuan awal bulan baru Ramadhan dan Syawal sangat penting bagi umat Islam karena berkaitan dengan waktu ibadah. Hakim syaraâ€™ Kesultanan Tidore (Joguru) telah lama mengaplikasikan metode penentuan awal bulan baru Hijriah (Ramadhan dan Syawal) melalui pergerakan pasang surut yang terpantau pada â€œakebaiâ€ termasuk dalam ethooceanography dan disebut dengan Metode Joguru (MJ). Hilal yang tidak pernah terlihat di wilayah Tidore dan sekitarnya selama siklus jangka panjang (34 tahun) menyebabkan hisab awal bulan tidak dapat diaplikasikan akibat tidak terpenuhinya persyaratan hisab (hadis). MJ melakukan pengÂamatan (rukyat) perubahan tinggi air pada â€œakebaiâ€ adalah â€œijtihadâ€. Terdapat keÂsesuaian aspek sains dari ethnoocaenography serta titik temu aspek syarâ€™i yang menjadikan MJ berpotensi sebagai metode utama sekaligus sebagai metode pemÂbanding dari metode umum dalam penentuan awal bulan baru Hijriah. Diperlukan perluasan makna kata â€œhilalâ€ sebagai indikator awal bulan baru penanggalan Hijriah.